2009
DOI: 10.1007/s11671-009-9396-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica: A Suitable Adsorbent for Amines

Abstract: Mesoporous silica with KIT-6 structure was investigated as a preconcentrating material in chromatographic systems for ammonia and trimethylamine. Its adsorption capacity was compared to that of existing commercial materials, showing its increased adsorption power. In addition, KIT-6 mesoporous silica efficiently adsorbs both gases, while none of the employed commercial adsorbents did. This means that KIT-6 Mesoporous silica may be a good choice for integrated chromatography/gas sensing micro-devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Chemisorption and physisorption of NH 3 on oxide material have been studied [12]. In the past literatures, it is reported that NH 3 was chemisorbed on silica surface forming the NH 3 -O-Si [19] or NH 2 -Si [20] with a siloxane bond (Si-O-Si).…”
Section: Adsorption Equilibrium Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Chemisorption and physisorption of NH 3 on oxide material have been studied [12]. In the past literatures, it is reported that NH 3 was chemisorbed on silica surface forming the NH 3 -O-Si [19] or NH 2 -Si [20] with a siloxane bond (Si-O-Si).…”
Section: Adsorption Equilibrium Studymentioning
confidence: 99%
“…The highly regular pore structure and internal surface area of ordered MS make these particles attractive substrates that can be tailored for NH 3 adsorption [8]. For example, MS particles showed very high uptake capacities and selectivities for CH 4 [9], CO 2 [10], H 2 S [11], NH 3 [12], and volatile organic vapors [13]. Few studies on the removal of hazardous gases by adsorption using MA are reported, even though MA and MS share similar pore properties and high thermal stabilities, as seen in comparison to reports about MS in the literature [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, several prerequisites need to be fulfilled for any practical use, including safe and efficient storage media with high volumetric uptakes, a facile cracking process, and an effective capture and removal system since even 1 ppm of NH 3 can poison proton exchange membrane fuel cells . A variety of materials have been investigated as storage and capture media for NH 3 , such as activated carbons, zeolites, , mesoporous silica, , and organic polymers. , Although porous materials as regenerable NH 3 capture systems have been demonstrated, many are limited by factors such as low storage capacity, irreversible uptake, and/or low packing density of stored NH 3 , which restrict their on-board applications due to the additional volume required for the storage system.…”
Section: Introductionmentioning
confidence: 99%
“…KIT-6 mesoporous silica is produced according to the procedures reported previously by Zamani et al [11] with some modifications. KIT-6 was synthesized in acidic conditions using a mixture of Pluronic P123 triblock copolymer (EO 20 PO 70 EO 20 ) and butanol.…”
Section: Preparation Of Kit-6 Silicamentioning
confidence: 99%